Peningkatan Dan Pengembangan Kompetensi Dasar Leadership Bagi Calon Leader "KAN Jabung Syariah Malang" Menggunakan Metode Problem Solving - Rini Agustina; Sovie Rosalin; San Rudiyanto; Okky Pramudiptha (JURNAL APLIKASI DAN INOVASI IPTEKS "SOLIDITAS" (J-SOLID), 2022)
KAN Jabung Syariah which is engaged in agribusiness and trade and services with a core business of dairy cows, and several other supporting business divisions that are developing require the improvement and development of the human resources of its members. Several potential human resources were appointed and selected from the staff level to be the next leader candidate. Leaders consider it necessary to provide a briefing to prospective leader candidates so that their basic competence, namely leadership, is fulfilled because this team does not only serve as routine extension workers but also as assistants. Basic leadership training is carried out through online mentoring for 2 months. The material provided is adjusted to the development of leadership, especially during the pandemic. The results of the training in the form of an increase in participants' understanding by 25% which were carried out through pretest and posttest during the training and the results of a participant satisfaction questionnaire of 85% stated that participants felt enlightened, additional knowledge and solutions to leadership problems. Most of them want similar training on a regular basis as motivation in their work.